Empowering the Jodipan Tourism Village (KWJ) through Information System Development to Enhance Tourist Visits in Malang City (Fakultas Teknik, Universitas Brawijaya, 2025)
Malang City possesses prominent tourism potential that can compete with other regions. Both domestic and international tourists consider Malang City as one of their preferred travel destinations. However, visitors often face challenges in finding routes and information about tourist attractions in the city. Therefore, it is crucial to provide efficient and accessible information for tourists. Kampung Wisata Jodipan (KWJ), a flagship attraction and a symbol of Malang City, has recently experienced stagnation and even a decline in visitor numbers. A proposed solution to address this issue is the development of an informative system to revitalize KWJ. This initiative aims to enhance KWJ's appeal through the development of an information system. Three main deliverables are expected to attract more visitors to KWJ: the Jodipan Tourism Village Route Map, the Jodipan Tourism Village Website, and the Operational Guidebook for the KWJ Website.